Coaxial Ag–Base Metal Nanowire Networks with High Electrochemical Stability for Transparent and Stretchable Asymmetric Supercapacitors - Park, Sangbaek (2017)
Transparent and stretchable Ag–Ni and Ag–Fe core–shell nanowire networks were fabricated as a cathode and anode, respectively, for asymmetric supercapacitors. Both electrodes showed a reversible stretchability at up to 100% strain and exhibited high electrochemical stability and specific capacitances of ∼3 mF cm−2 with 50% optical transmittance. The asymmetric device assembled with a PVA/KOH electrolyte demonstrated a high operating voltage of 1.6 V and an excellent capacitance retention (92%) over 5000 cycles even after stretching to 35% strain.